LEMBUSUANA SIMBUL KEKUATAN DAN KEKUASAAN RAJA KUTAI - Awang Muhammad Rifani (MAHAKAM: Jurnal Ilmu-Ilmu Sosial, 2013)
Lembusuana is a fabulous and extraordinary creature as the secret of nature, the possessor of all the elements of life and power to be the spirit and the resource of inspirationKey words: Lembusuana